Tensile and impact properties of pulverized oil palm fiber reinforced polypropylene composites: A comparison study with wood fiber reinforced polypropylene composites - Nordin, Mohd Nur Azmi; Goda, Kohichi; Azhari, Muhamad Haikal; Kenji, Sakamoto; Okamoto, Masaki; Ito, Hirokazu; Endo, Takashi (Universiti Malaysia Pahang, 2018)
The comparison of tensile and impact properties between the fiber extracted from Malaysia’s oil palm plantation wastes and residues and wood fiber that are going to be used as reinforcing agent in polymer composite materials is the main focus of this study. For that purpose, 10 wt.% and 25 wt.% of Malaysian oil palm fiber (OPF) extracted from oil palm empty fruit bunches (OPEFB) was incorporated with polypropylene (PP) and maleated polypropylene (MAPP) to produce injection-molded composite materials. For comparison purposes, virgin PP and wood fiber reinforced polymer composites (WPC)were also fabricated as benchmark samples. Firstly, tensile test was performed for all three samples; virgin PP, OPF/PP and WPC in order to investigate the effect of fiber loading on composite materials. From the tensile test result, 25 wt.% of fiber loading produced higher tensile properties than 10 wt.% of fiber loading. Moreover,the obtained OPF/PP composites showed comparable properties with the WPC material. Furthermore, the effect of fiber size on tensile and impact properties of both OPF/PP and WPC composite was investigated. As the results, the utilization of OPF into PP matrix demonstrated almost similar tensile and impact strength as WPC material. The equality of properties between OPF/PP composites and WPC indicates the potential of wastes and residual materials such as OPF to be broadly utilized in the production of composite materials.